Trichoderma reesei JCM 2267, fungi-associated sponge Stylissa flabelliformis: Effects of applied different fermentation methods on their antibacterial activity - Dyan Wigati; Erna Prawita Setyowati; Prawita Erna; Sylvia Utami Tunjung Pratiwi; Ari Satia Nugraha (Journal of Advanced Pharmaceutical Technology & Research, 2024)
Trichoderma is one of the fungi producing a wide range of metabolites with potent biological activities, including antibacterial. Selecting appropriate fermentation methods can improve the production of metabolite compounds and provide the best biological activity. This study investigates Trichoderma reesei JCM 2267’s antibacterial activity, which is fermented using submerged fermentation (SmF) and solid-state fermentation (SSF). The effect of fermentation time on antibacterial activities and yield weight was also determined. Antibacterial activity was tested against Staphylococcus aureus (S.a) ATCC 25923, Escherichia coli (E.c) ATCC 25922, and Pseudomonas aeruginosa (P.a) ATCC 27853 using the Agar well diffusion method. This research successfully demonstrated that the SmF and SSF methods provided extracts with antibacterial activity ranging from weak to strong, against bacteria tested. The extract fermented by SSF showed the best activity on day 25 of fermentation with a diameter clear zone 12.2 ± 0.20; 5.0 ± 0.17, and 3.3 ± 0.1 (mm) against S.a ATCC 25923, E.c ATCC 25922, and P.a ATCC 27853. The extract fermented by SmF, especially the supernatant extract, reached the higher inhibition on day 8 with diameter inhibition 6.90 ± 0.05 and 8.20 ± 0.04 (mm) against E.c ATCC 25922 and P.a ATCC 27853, whereas 15.3 ± 0.10 (mm) against S.a ATCC 25923 on day 14 of fermentation. The various times of fermentation affect the antibacterial activities. The maximum growth of TR JCM 2267 was reached on day 14 of fermentation. The SSF methods showed a higher yield of extract than SmF, increasing over time of fermentation. This research provides a possible alternative fermentation method suitable for fungal growth related to its antibacterial activity and extract yield.